The Novelty of Phenomenological Sociology and Its Interdisciplinarity. An interview to professor Carlos Belvedere - Ferri, Michela Beatrice (SocietàMutamentoPolitica, 2016)
Carlos Belvedere is a Researcher of the National Council for Technical and Scientific Research (CONICET) at the Gino Germani Research Institute, and a Professor at the University of Buenos Aires (UBA) and the National University of General Sarmiento (UNGS). He is a member of the Society for Phenomenology and the Human Sciences (SPHS), which he has co-chaired since 2014, and an Editorial Board member of «Human Studies», the official journal of SPHS. He is also a founding member of The International Alfred Schutz Circle for Phenomenology and Interpretive Social Science. He has authored a number of papers and books on Social Phenomenology dealing with fundamental problems in the Philosophy and theory of the Social Sciences.